Rrp6 Regulates Heterochromatic Gene Silencing via ncRNA RUF6 Decay in Malaria Parasites - Fan, Yanting (mBio, 2020)
The heterochromatin environment plays a central role in silencing genes associated with the malaria parasite’s development, survival in the host, and transmission to the mosquito vector. However, the underlying mechanism regulating the dynamic chromatin structure is not understood yet. Here, we have uncovered that Plasmodium falciparum Rrp6, an orthologue of eukaryotic RNA exosome-associated RNase, controls the silencing of heterochromatic genes. PfRrp6 knockdown disrupted the singular expression of the GC-rich ncRNA RUF6 family, a known critical regulator of virulence gene expression, through the stabilization of the nascent transcripts. Mechanistic investigation showed that the accumulation of the multiple RUF6 ncRNAs triggered local chromatin remodeling in situ, which activated their adjacent var genes. Strikingly, chromatin isolation by RNA purification analysis (ChIRP-seq) revealed that a remarkable RUF6 ncRNA had interacted with distal heterochromatin regions directly and stimulated a global derepression effect on heterochromatic genes, including all variant gene families and the sexual commitment-associated regulator ap2-g gene. Collectively, Rrp6 appears to conduct the epigenetic surveillance of heterochromatic gene expression through controlling RUF6 levels, thereby securing antigenic variation and sexual commitment of malaria parasites during the infection of the host.